HIDROLISIS SELULOSA DARI SEKAM PADI (Oryza sativa) MENJADI GLUKOSA DENGAN KATALIS ARANG TERSULFONASI - Adeks Pramana; Abdul Rahman Razak; Prismawiryanti Prismawiryanti (KOVALEN: Jurnal Riset Kimia, 2016)
Cellulose hydrolysis from rice husk (Oryza sativa) into glucose with sulfonated charcoal catalyst was conducted. The aim of this research was to determine sulfuric acid concentration and contact time on the sulfonation process of charcoal which would produce the highest glucose rendement from cellulose hydrolysis of rice husk. Sulfuric acid concentrations in this experiment were 8, 10, and 12 N with variation of contact time of 4, 6, 8, 10 and 12 hours respectively.  Rice husk was delignified with NaOH 10% to produce cellulose which was hydrolyzed by sulfonated charcoal catalyst. Hydrolysis reaction with the ratio cellulose/aquadest 1:25 (w/v) was conducted in autoclave with temperature 130 oC for 3 hours. The result showed that 8 N concentration of sulfuric acid and 12 hours of contact time produced the highest glucose rendement 17,9%. Keywords : rice husks, cellulose, glucose, sulfonated charcoal